Meningkatkan Ketrampilan Lulusan melalui Pengembangan Kurikulum Pastoral Konseling Berdasarkan Merdeka Belajar dan Kampus Merdeka dalam Kegiatan Magang di Institut Agama Kristen Negeri Tarutung - Malau, Oloria; Sihombing, Robinhot; Sitompul, Sabar Rudi; Sipahutar, Melina Agustina (SEKOLAH TINGGI AGAMA KRISTEN TERUNA BHAKTI, 2022)
In accordance with the current independent learning program and independent campus, especially in the implementation of internships/work practices, the existing Pastoral Counseling study program curriculum has the potential to be developed. In order to achieve graduates of the IAKN Tarutung Pastoral Counseling Study Program who are skilled in mentoring in accordance with the expectations of the achievement of the graduate profile and able to achieve the IAKN Tarutung mission. The purpose of this research is to develop a Pastoral Counseling Curriculum based on the Independent Learning and Independent Campus in Internship/Work Practice activities. This article uses research and development (R&D) methods. Referring to the results of the Curriculum expert validator regarding the development of the Pastoral Counseling study program curriculum based on the Merdeka Learning Independent Campus in the internship/work practice at the Faculty of Theological Sciences, IAKN Tarutung, it was concluded that it is suitable for use in learning Pastoral Counseling study programs with eligibility criteria levels 85, 96 %. Likewise, based on the results of the assessment of Pastoral Counseling expert validators/internship partners in terms of curriculum development research, it was concluded that it was suitable for use in Pastoral Counseling study program learning with a level of eligibility criteria of 85, 67%. With the conclusion that the curriculum development presented in this study is feasible to use and